Utilization of sweet potato as a forage supplement to a maize stover diet by West African dwarf sheep (2005)
In a growth and digestibility trial with West African dwarf sheep (WAD) the effects of supplementing maize stover with four levels of sweet potato forage (0, 1, 2 and 3% of body weight) on intake and growth rate of the animals; and digestibility of maize stover, sweet potato forage and their mixture were determined using a randomized complete block and completely randomized design, respectively. The dry matter (DM) intake and growth rate of the animals improved significantly (P < 0.01) with increasing level of sweet potato forage in the diet. DM intake was highest at the highest level (3% BW) of sweet potato inclusion and was 140% of the sole maize stover diet. Growth rate of animals at 3% (BW) level of sweet potato supplementation was 195% better than that of animals on sole maize stover. Digestibility of sheep diet improved significantly (P < 0.05) when sweet potato forage formed whole or part of the diet. Addition of sweet potato forage to a basal diet of maize stover improved animal productivity from this fibrous crop residue.